2015
DOI: 10.1155/2015/965825
|View full text |Cite
|
Sign up to set email alerts
|

The Links between Energy Consumption, Financial Development, and Economic Growth in Lebanon: Evidence from Cointegration with Unknown Structural Breaks

Abstract: We investigate the relation between financial development, energy consumption, and economic growth in the economy of Lebanon over the period 2000M 2 -2010M 12 . Our findings confirm the existence of cointegration among the variables. The results indicate that financial development and energy consumption contribute to economic growth in Lebanon. The impact of energy consumption on economic growth is positive showing the significance of energy as a main stimulant of economic growth. Financial development is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…In the context of finance and energy, many empirical studies, like Sadorsky [6] for 22 emerging countries, Xu [25] for China, Shahbaz et al [26] for Indonesia, Coban and Topcu [27] for EU countries, Islam et al [28] for Malaysia, Ozturk and Acaravci [29] for Turkey, Tang and Tan [30] for Malaysia, Salah et al [31] for Lebanon found the positive impact of financial development on energy consumption.…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 99%
“…In the context of finance and energy, many empirical studies, like Sadorsky [6] for 22 emerging countries, Xu [25] for China, Shahbaz et al [26] for Indonesia, Coban and Topcu [27] for EU countries, Islam et al [28] for Malaysia, Ozturk and Acaravci [29] for Turkey, Tang and Tan [30] for Malaysia, Salah et al [31] for Lebanon found the positive impact of financial development on energy consumption.…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 99%
“…The study found a bidirectional causal link between Þ nancial development as measured by stock market indicators and energy consumption in the case of Algeria. Abosedra et al (2015) investigated the relationship between Þ nancial development and energy consumption for Lebanon and found a bidirectional causal link between the two variables. The study applied the Vector Error Correction based Granger-causality test on monthly data over the period 2000 to 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, the majority of the empirical studies that have been conducted on the relationship between Þ nancial development and energy consumption are mainly concentrated in the Asian and Latin-American countries (see Abosedra et al, 2015;Furuoka, 2015;Kakar, 2016;Sbia et al, 2017). Very few empirical studies on this subject exist for the sub-Saharan African countries.…”
Section: Introductionmentioning
confidence: 99%
“…2013), (Rasoulinezhad and Saboori, 2018), (Tiba and Frikha, 2018). iii) neutrality hypothesis; the fact that the share of energy consumption in total output is very small infers that there is no causal relationship between energy consumption and economic growth (Menegaki, 2011), (Menyah and Wolde-Rufael, 2010), (Abosedra, Shahbaz and Sbia, 2015), (Acaravci and Ozturk, 2010), (Odhiambo, 2009). iv) the protection hypothesis; one-way causality relation from economic growth to energy consumption, and the increase in real GDP leads to an increase in energy consumption (Gurgul and Lach, 2012), (Sadorsky, 2009), (Esso, 2010), (Apergis and Payne, 2009).…”
Section: Energy Consumption and Economic Growthmentioning
confidence: 99%